Evaluation of surgical cavities filled with three types of calcium sulfate - Sergio Toshinori Maeda; Clovis Monteiro Bramane; Rumio Taga; Roberto Brandão Garcia; Ivaldo Gomes de Moraes; Norberti Bernadineli (University of São Paulo, 2007)
The aim of this study was to evaluate histologically, three types of calcium sulfate - Merck (Brazil), Surgiplaster (Italy) and Capset (USA) - in surgically created defects on rabbit femurs. Twenty male New Zealand rabbits were used. Two surgical bone defects (5 mm diameter x 8 mm depth) were created on each distal epiphysis using a #3 Dentoflex trephine bur. Defects were filled with: group 1 - di-hydrated calcium sulfate (Merck); group 2 - Capset (Lifecore-USA); group 3 - Surgiplaster (Classimport-Italy); group 4 - control (blood clot). The animals were sacrificed 30, 60, 90 and 180 days postoperatively. Semi-serial 6-mm-thick sections were obtained, stained with hematoxylin and eosin and examined under light microscopy. Bone defects treated with calcium sulfate exhibited new bone formation regardless of the product trademark.